Transmedia a sztuka Roberta Wilsona - Jelewska, Agnieszka (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Transmedia and Robert Wilson’s Art Robert Wilson’s works have been discussed here in the historical-artistic context of the 20th century and in reference to the modern theories of the media, which use such terms as “transmediality” and “media landscape”. The intermedial model of arts has been exhausted and there has appeared the problem of transmediality, as well as such issues like transcegenity, transinstrumentality, transperception and even transcompetence of art. Technologies which developed in the 20th century and media codes, redefined and new, provoked a change of thinking about the theatre and every other art which uses various instruments. R. Wilson – like other artists who exist in the transmedial net – sees the theatre through audiovisual arts and film; he does not introduce them to his performances but uses their tools and specific narrations characteristic for the arts.